Genomic Analyses Reveal Adaptation to Hot Arid and Harsh Environments in Native Chickens of China - Gu, Jingjing; Liang, Qiqi; Liu, Can; Li, Sheng (Frontiers in Genetics, 2020)
The acute thermal response has been extensively studied in commercial chickens because of the adverse effects of heat stress on poultry production worldwide. Here, we performed whole-genome resequencing of autochthonous Niya chicken breed native to the Taklimakan Desert region as well as of 11 native chicken breeds that are widely distributed and reared under native humid and temperate areas. We used combined statistical analysis to search for putative genes that might be related to the adaptation of hot arid and harsh environment in Niya chickens. We obtained a list of intersected candidate genes with log2 θπ ratio, FST and XP-CLR (including 123 regions of 21 chromosomes with the average length of 54.4kb) involved in different molecular processes and pathways implied complex genetic mechanisms of adaptation of native chickens to hot arid and harsh environments. We identified several selective regions containing genes that were associated with the circulatory system and blood vessel development (BVES, SMYD1, IL18, PDGFRA, NRP1 and CORIN), related to central nervous system development (SIM2 and NALCN), related to apoptosis (CLPTM1L, APP, CRADD and PARK2) responded to stimuli (AHR, ESRRG FAS and UBE4B) and involved in fatty acid metabolism (FABP1). Our findings provided the genomic evidence of the complex genetic mechanisms of adaptation to hot arid and harsh environments in chickens. These results may improve our understanding of thermal, drought, and harsh environment acclimation in chickens and may serve as a valuable resource for developing new biotechnological tools to breed stress-tolerant chicken lines and or breeds in the future.